Status Report Joint Village Participatory Land Use Planning (JVLUP) and Participatory Rangeland Management (PRM) Sites Tanzania 2022 - International Livestock Research Institute (International Livestock Research Institute, 2022)
Piloting participatory rangeland management (PRM) in Tanzania and Kenya was a 48-month EU-funded project. The project ran from December 2017 to December 2021. Its overarching goal was to improve the livelihood and nutrition status of pastoralist communities in East Africa by improving rangeland management to secure and better use rangelands and expand the role of women in selected pastoral communities in Kenya and Tanzania. The project was coordinated by the International Land Coalition (ILC), hosted at IFAD, and implemented by a diverse partnership comprising the Resource Conflict Institute (RECONCILE) as the in-country lead in Kenya, the Tanzania Natural Resource as the in-country lead in Tanzania, the International Livestock Research Institute providing technical support, Vétérinaires Sans Frontières linking the project with the Coalition of European Lobbies on Pastoralism in East Africa and SOS SAHEL providing opportunities for learning about participatory rangeland management based on their experience in Ethiopia.